Teachers' opinions on the competencies needed by elementary school principals in Camarines Norte, 1969-1970 - Dating, Agustin A. 1928- (s.n.], 1971)
The opinions of teachers on the competencies needed by elementary school principals in the Division of Camarines Norte,the extent to which they are needed, and their implications for the school's administration and supervision were obtained in this study. The normative survey or descriptive method was utilized, with a questionnaire and interview as tools. In the opinion of the teachers, 41 out of the 50 specific competencies a principal should possess are considered slightly needed by principals in the Division of Camarines Norte.